Estrategias preventivas de depresión en adultos mayores que asisten al centro geronto-geriátrico, “Hermana Gabriela Zapata” de la ciudad Francisco de Orellana, 2016 - Chapués Cumabalaza, Alexandra del Pilar (2016)
This study was conducted at the Gerontological Centre - Geriaiic Sister Gabriela Zapata, city Orellana, which aims to implement preventive strategies of depression in older adults attending care center for the elderky, since according to various studies the incidence of this disease may decrease f the risk factors is prevented; considermg that depression is a common problem overall. The methodology applied was qual type - quantitatve and field, such as technical survey was used, using the test Yesavage and interview aimed al health professionals, to determine the level of depression thai presents the study population; deductive, analytical - - Synihetic, historical - logical and systemic besides theoretical methods such as inductive method was used. This research projeat is framed on the subject of study and research online healih management and disease prevention. As a result of the investigation ii was identiñed that half of older adults have a mild depression type, since are just starting to live this las! stage of fe; instead a quarter, if has severe depression, showing clear symptoms of the disease where the person constantly has deep feelings of sadness, lack of motivation and low self-esteem. Because of these results it is designed preventive strategies based on leisure and recreational seniors who attend the center of the elderly activities; among the main beneficiaries are the elderly and their famibes.